Club Cell Protein 16 Attenuates CD16brightCD62dim Immunosuppressive Neutrophils in Damaged Tissue upon Posttraumatic Sepsis-Induced Lung Injury - Nils Becker; Philipp Störmann; Andrea Janicova; Kernt Köhler; Klemens Horst; Ildiko Rita Dunay; Claudia Neunaber; Ingo Marzi; Jan Tilmann Vollrath; Borna Relja (Journal of Immunology Research)
Background. Recently, identification of immunosuppressive polymorphonuclear leukocytes (PMNL) that were traditionally described as proinflammatory cells emerged in the field of posttraumatic immunity. To understand their local and remote distribution after trauma, PMNL-subsets and the impact of immunomodulatory Club Cell protein (CC)16 that correlates with pulmonary complications were assessed. Methods. C57BL/6N mice were divided into three groups, receiving isolated blunt chest trauma (TxT), undergoing TxT followed by cecal ligation and puncture (CLP, TxT+CLP) after 24 h, or sham undergoing analgosedation (n=18/group). Further, each group was subdivided into three groups receiving either no treatment (ctrl) or intratracheal neutralization of CC16 by application of anti-CC16-antibody or application of an unspecific IgG control antibody (n=6/group). Treatment was set at the time point after TxT. Analyses followed 6 h post-CLP. PMNL were characterized via expression of CD11b, CD16, CD45, CD62L, and Ly6G by flow cytometry in bone marrow (BM), blood, spleen, lung, liver, and bronchoalveolar and peritoneal lavage fluid (BALF and PL). Apoptosis was assessed by activated (cleaved) caspase-3. Results from untreated ctrl and IgG-treated mice were statistically comparable between all corresponding sham, TxT, and TxT+CLP groups. Results. Immature (CD16dimCD62Lbright) PMNL increased significantly in BM, circulation, and spleen after TxT vs. sham and were significantly attenuated in the lungs, BALF, PL, and liver. Classical-shaped (CD16brightCD62Lbright) PMNL increased after TxT vs. sham in peripheral tissue and were significantly attenuated in circulation, proposing a trauma-induced migration of mature or peripheral differentiation of circulating immature PMNL. Immunosuppressive (CD16brightCD62Ldim) PMNL decreased significantly in the lungs and spleen, while they systemically increased after TxT vs. sham. CLP in the TxT+CLP group reduced immunosuppressive PMNL in PL and increased their circulatory rate vs. isolated TxT, showing local reduction in affected tissue and their increase in nonaffected tissue. CC16 neutralization enhanced the fraction of immunosuppressive PMNL following TxT vs. sham and decreased caspase-3 in the lungs post-CLP in the TxT+CLP group, while apoptotic cells in the liver diminished post-TxT. Posttraumatic CC16 neutralization promotes the subset of immunosuppressive PMNL and antagonizes their posttraumatic distribution. Conclusion. Since CC16 affects both the distribution of PMNL subsets and apoptosis in tissues after trauma, it may constitute as a novel target to beneficially shape the posttraumatic tissue microenvironment and homeostasis to improving outcomes.